Gambaran Perilaku Sedentary, Aktivitas Fisik, dan Status Gizi Siswa MTs Pulau Pandan Kabupaten Kerinci - Yusi Yuwanda; Andicha Gustra Jeki; Nel Efni; Maryam Novita Sari (3031-8572, 2025)
Adolescents are a vulnerable age group to nutritional problems due to physiological changes and lifestyle, including increased sedentary behasvior and low physical activity. Thisstudy aimed to describe sedentary behavior, physical activity, and nutritional status among students at MTsS Pulau Pandan, Kerinci Regency. This descriptive quantitative study used a cross-sectional design. The sample consisted of all 40 seventh-grade students selected using total sampling. Sedentary behavior data were obtained using the ASAQ questionnaire, physical activity using the PAL questionnaire, and nutritional status measured using body mass index for age (BMI/A). Results showed that 60% of students had moderate sedentary behavior, 35% low, and 5% high. Physical activity was mostly in the light (45%) and moderate (40%) categories, with 15% high. Nutritional status showed 60% normal, 15% overweight, 12.5% obese, and 12.5% undernourished. In conclusion, high sedentary behavior and low physical activity have the potential to affect adolescents’ nutritional status. Interventions such as nutrition education and increasing physical activity are necessary to prevent nutritional problems.